The iridium-catalysed alkylation of aromatic ketones via hydrogen borrowing - Cheong, C (2018)
This dissertation explores how the scope of hydrogen borrowing reactions can be further expanded to use both primary and secondary alcohols to form α-, β- and α,β-branched aryl ketones. ortho Substituents were critical in enabling the hydrogen borrowing alkylation by inducing a non-coplanar geometry of the aryl–ketone motif, which provides various beneficial effects that contribute to the success of the reaction. The versatility of the hydrogen borrowing reaction was further improved by introducing a vinylcyclopropane rearrangement into the reaction manifold prior to enone reduction. Control studies and modified substrate provide insight into the mechanism of the reaction. The synthetic utility of pentamethylphenyl (Ph*) ketones was enhanced through electrophilic cleavage to form various carboxylic acid derivatives. Phenol derivatives of Ph* ketones were also found to undergo a related oxidative cleavage of the derivatised Ph* group to form esters and carboxylic acids. Phenol and aniline derivatives of Ph* ketones formed tetrasubstituted α-keto centres in the hydrogen borrowing reaction, a remarkable result that could not have been possible using conventional aldol chemistry. Attempts were made to explore the formation of tetrasubstituted α-keto centres in the hydrogen borrowing reaction with other aryl ketone derivatives. Structural changes were observed by X-ray crystallography that were consistent with the alleviation of steric interactions between the aryl group and ketone substituent, providing evidence that ortho-substitution provides multiple benefits that drive the hydrogen borrowing reaction. Substituents at the meta and para positions of the aryl ring result in structural distortions that are directly responsible for the "buttressing" effect. IR, 13C and 15N NMR spectroscopy were also employed to study the effects of non-coplanar geometries of the amino, nitro and carbonyl groups.